Eventyret Norsk Moskus A/S: Norsk Moskus (Norwegian Muskox) A/S a project like no other - Schytte Blix, Arnoldus (Rangifer, 2023)
Norsk Moskus A/S was, for good or worse, Alfred Henningsen’s own private eterprise. It was by many, probably also by Henningsen himself, judged as a failure. That is hardly the full story. The project was inspired from USA, where a similar project was already under way with the purpose to domesticate the muskox to improve the economic and social conditions of native arctic people by using the wool to produce garment for sale. In addition, Henningsen wanted to secure the economy by tourism based on public interest in the animals. He also approached the new university in Tromsø for cooperation from the very beginning. The operation was established in Bardu in northern Norway and had several shortcomings already from the beginning in 1969. It had no financial base whatsoever, as Henningsen assumed that his connections as member of Parliament would soon provide the cash. That did not happen. The information from USA was (quite erroneously) that domestication of muskox was very easy, and therefore, and because of bad economy, no relevant husbandry expertice was involved. Instead, the project was managed by amateurs and enthusiastic volunters. The expected cooperation with research institutions did not materialise either. In spite of this, the project took off rather well during the first few years. Calf production was good, wool and garment production was well under way and tourists brought in the cash. Even so, because of the need for heavy infrastructure investments they were always economically behind, and very soon had to sell animals to avoid bankrupsy. 1975 became a turningpoint. At that time they were hit by a massive outbreak of Contagious echtyma which killed all the calves and half of the adult bulls, and a local resident was killed by a bull which had escaped from the farm. The latter turned a hitherto positive attitude among the locals to become rather hostile, and necessitated a move of the whole operation to Årøya in Kvænangen where the locals were still positive in 1976. The relocation inflicted new heavy infrastructure investments which was financed by the sale of several of the remaining animals, but the relocation was, at first, nevertheless, a success, and everything looked bright for the 1977 season. However, just before the opening the Ministry of Agriculture decided, with reference to new legislation, to ban public showing of the animals. The decision was appealed, but was in the end turned down in a decision by, no less than, the King in Cabinet. After much politicking, however, a temporary permit was granted in 1979, but at that time the project was economically at rock bottom, and a new bridge which led the tourist trafic away from the farm had materialized. After fighting for 20 years Henningsen then gave up and donated the 10 remaining animals to the Department of Arctic Biology at the University of Tromsø. The University consequently set up a farm at Rya island outside Tromsø, where they trived and for 40 years were used for reseach, and thereby fullfilling one of the most important original intensions of the project.